Using MOOCs at Learning Centers in Northern Sweden - Anders Norberg (Athabasca University Press, 2015)
This paper describes the use of globally accessible Massive Open Online Courses, MOOCs, for addressing the needs of lifelong learners at community learning centers in Northern Sweden, by the forming “glonacal” or “blended” MOOCs. The Scandinavian “study circle” concept is used to facilitate the studying of MOOCs. Although the technical possibilities for Swedish universities to offer accessible education are constantly increasing, most Swedish universities do not, at present, prioritize courses for off-campus students. The available web courses in asynchronous formats are difficult to master for untraditional learners and leaves the learning centers with limited possibilities. Therefore, a Nordplus Horizontal project 2014-2016 with partners in three Nordic countries is developing models for the use of MOOCs in learning centers and organisations. A small pilot course case at the learning centre in Arvidsjaur and its outcomes is presented, including the interactions with Lund University which has an ongoing piloting project on use and examination of MOOCs. This concept development is discussed as a blended learning design and as a “glonacal” phenomenon with Marginson and Rhoades’ “glonacal agency heuristics” (2002) forming a background for an actor analysis. Future scenarios are outlined.